Efectuati:
a) (2√3+x)²=
b) (3√3x+2√5)²=
c) (½x+3)²=
d) (3-2√3)²=
e) (2√5x-3√2x)²=
f) (5√2x-4√3y)²=
g) (8x-4√5)(8x+4√5)=
h) (7√2a-5√6b)(7√2a+5√6b)=
i) (√2x-3y)(√2x+3y)=
j) (⅓x-3\2)²=
k) (√2/2x+1\√2y)²=
l) (⅓x-5/6yz)(⅓x+5/6yz)=
m) (x-3)(x+3)(x²+9)-(x²+9)-(x²+2)²+3(x-1)²=
n) (x+5)(x²-1)-x(x+4)²+(x-1)²=
o) (3xy-5)(3xy+5)-(3xy-2)²=
p) (5x-8)[2(x+1)+3(x+2)]-(3x-4)[5(x+2)-2(x+3)]=
q) (7√3+√2)²-2(1+7√6)=
r) 2√5(√3-1)+(√5-√3)²=
s) 12√75+(6-5√3)²=
ș) (3√7-2√6)²+60√126:(5√3)=
t) (3√5-√15)(3√5+√15)-2(√6+1)²=
Răspunsuri la întrebare
Răspuns de
45
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă